2009
DOI: 10.1002/ajhb.20887
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ghrelin concentration is a signal of decreased fat free mass in healthy elderly females

Abstract: This study aimed to evaluate whether circulating ghrelin is associated with changes in different body composition parameters over a 12-month prospective study period in healthy older females. On 41 postmenopausal women (mean age: 71.0 +/- 6.5 years), ghrelin, leptin, insulin resistance (IR), and body composition parameters were assessed before and after the study period. Trunk fat: leg fat ratio (+3.6%), fat free mass (FFM) (-4.1%), glucose (+5.8%), and IR (+7.0%) were significantly changed (P < 0.05), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This data indicates that ghrelin is a functional regulator of nutritional status in ageing men and that ghrelin activity may protect against malnutrition in this gender, but that women may be unprotected by this mechanism. 31 However, when examining the relationship between weight loss and GH circulating concentrations, we found different situations according to gender: in 70-to 80-year-old men, weight loss was related to higher basal GH and lower basal testosterone, whereas in women, weight loss was associated with low GH. This could be due to a lower number of subjects included in this age range in our study, or just because at a certain age this hormonal mechanism loses its regulatory effect on nutrition homeostasis.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This data indicates that ghrelin is a functional regulator of nutritional status in ageing men and that ghrelin activity may protect against malnutrition in this gender, but that women may be unprotected by this mechanism. 31 However, when examining the relationship between weight loss and GH circulating concentrations, we found different situations according to gender: in 70-to 80-year-old men, weight loss was related to higher basal GH and lower basal testosterone, whereas in women, weight loss was associated with low GH. This could be due to a lower number of subjects included in this age range in our study, or just because at a certain age this hormonal mechanism loses its regulatory effect on nutrition homeostasis.…”
Section: Discussionmentioning
confidence: 80%
“…7 A recent prospective study also showed that low ghrelin concentration can predict a loss in fat-free mass in elderly women. 31 However, when examining the relationship between weight loss and GH circulating concentrations, we found different situations according to gender: in 70-to 80-year-old men, weight loss was related to higher basal GH and lower basal testosterone, whereas in women, weight loss was associated with low GH. The explanation to this observation may be related to a different gonadal hormonal profile and stress response profile between genders.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The age-related changes in body composition are caused by a reduction in specific anabolic hormones and also in physical activity (PA) level (Bertoli et al 2006;Jürimäe et al 2009c). A decreased total PA level has been associated with increased risk of having cardiovascular disease in older people (Aoyagi and Shephard 2009;Yu et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is a hormone produced by the stomach that stimulates appetite and has been shown to correlate with loss of fat-free mass in older adults [7]. In a recent study, Serra-Prat et al [8, 9] found that in frail older adults (>75 yrs of age), levels of fasting ghrelin were lower than similar age nonfrail older adults.…”
Section: Introductionmentioning
confidence: 99%